2015
DOI: 10.1159/000370225
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case Involving a Female Patient with Upshaw-Schulman Syndrome: Low Titers of Antibodies against ADAMTS13 prior to Pregnancy Disappeared after Successful Delivery

Abstract: Background: Upshaw-Schulman syndrome (USS) is usually suspected based on severe deficiency of ADAMTS13 activity without ADAMTS13 antibody, but the definitive diagnosis is made by ADAMTS13 gene analysis. We present a unique case of USS with low titers of ADAMTS13 antibodies before pregnancy. Interestingly, titers of ADAMTS13 antibodies decreased to almost undetectable levels after delivery. Case Report: In patient LL4, the diagnosis of USS was confirmed at age 27 by ADAMTS13 gene analysis. She became pregnant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The characteristics of these patients and babies are shown in Table 1, and for some of them the detailed clinical course during pregnancy was previously reported. 7,9,[17][18][19][20][21] Each mother's cTTP code corresponded to those in our previous reports. 3,7,9,11,22 We classified these 38 pregnancies into two groups.…”
Section: Study Design and Enrollmentmentioning
confidence: 80%
See 1 more Smart Citation
“…The characteristics of these patients and babies are shown in Table 1, and for some of them the detailed clinical course during pregnancy was previously reported. 7,9,[17][18][19][20][21] Each mother's cTTP code corresponded to those in our previous reports. 3,7,9,11,22 We classified these 38 pregnancies into two groups.…”
Section: Study Design and Enrollmentmentioning
confidence: 80%
“…Because early miscarriage sometimes occurs even in healthy women (10%‐15%), 16 we excluded miscarriages (n = 2) before 12 weeks of gestation. The characteristics of these patients and babies are shown in Table 1, and for some of them the detailed clinical course during pregnancy was previously reported 7,9,17‐21 . Each mother's cTTP code corresponded to those in our previous reports 3,7,9,11,22 …”
Section: Methodsmentioning
confidence: 99%
“…However, some rare cases of congenital TTP patients presenting with anti-ADAMTS13 autoantibodies have been described. 7 8 9 On the other hand, two sisters have been reported who had acquired immune-mediated TTP, although their familial history was suspicious for congenital TTP. 10 Hence, it was suggested that investigating the presence of both anti-ADAMTS13 autoantibodies and ADAMTS13 genetic variations is sometimes essential to improve the differential diagnosis between immune-mediated TTP and congenital TTP.…”
Section: Introductionmentioning
confidence: 99%